Interaction of lysozyme with a tear film lipid layer model: A molecular dynamics simulation study - Wizert, Alicja; Iskander, D Robert; Cwiklik, Lukasz (Biochimica et biophysica acta. Biomembranes, 2017)
The tear film is a thin multilayered structure covering the cornea. Its outermost layer is a lipid film underneath of which resides on an aqueous layer. This tear film lipid layer (TFLL) is itself a complex structure, formed by both polar and nonpolar lipids. It was recently suggested that due to tear film dynamics, TFLL contains inhomogeneities in the form of polar lipid aggregates. The aqueous phase of tear film contains lachrymal-origin proteins, whereby lysozyme is the most abundant. These proteins can alter TFLL properties, mainly by reducing its surface tension. However, a detailed nature of protein-lipid interactions in tear film is not known. We investigate the interactions of lysozyme with TFLL in molecular details by employing coarse-grained molecular dynamics simulations. We demonstrate that lysozyme, due to lateral restructuring of TFLL, is able to penetrate the tear lipid film embedded in inverse micellar aggregates.
Keywords: sfingomyeliny; Triolein; Tear film; Lipid-protein interaction; Humans; fosfatidylcholiny; Tear film lipid layer; termodynamika; Phosphatidylethanolamines; fosfatidylethanolaminy; sulfoglykosfingolipidy; triolein; Lysozyme; Molecular dynamics; lidé; Sulfoglycosphingolipids; simulace molekulární dynamiky; Kinetics; Thermodynamics; Adsorption; Surface Tension; Molecular Dynamics Simulation; estery cholesterolu; voda; Muramidase; Cholesterol Esters; Tears; povrchové napětí; Phosphatidylcholines; Water; adsorpce; muramidasa; slzy; Sphingomyelins; kinetika